Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's find the product of the expression [tex]\((x \sqrt{7} - 3 \sqrt{8}) (x \sqrt{7} - 3 \sqrt{8})\)[/tex].
To do this, we will use the formula for expanding a binomial squared: [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]. In our case, [tex]\(a = x \sqrt{7}\)[/tex] and [tex]\(b = 3 \sqrt{8}\)[/tex].
First, let's identify and compute the three terms in the expanded form individually.
1. Calculate [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = (x \sqrt{7})^2 = x^2 \cdot (\sqrt{7})^2 = x^2 \cdot 7 = 7x^2 \][/tex]
2. Calculate [tex]\(b^2\)[/tex]:
[tex]\[ b^2 = (3 \sqrt{8})^2 = 9 \cdot (\sqrt{8})^2 = 9 \cdot 8 = 72 \][/tex]
3. Calculate [tex]\(-2ab\)[/tex]:
[tex]\[ 2ab = 2 \cdot (x \sqrt{7}) \cdot (3 \sqrt{8}) = 2 \cdot x \cdot \sqrt{7} \cdot 3 \cdot \sqrt{8} = 6 \cdot x \cdot (\sqrt{7} \cdot \sqrt{8}) \][/tex]
We know that [tex]\(\sqrt{7} \cdot \sqrt{8} = \sqrt{56} = \sqrt{4 \cdot 14} = 2 \sqrt{14}\)[/tex]. So:
[tex]\[ 2ab = 6 \cdot x \cdot 2 \sqrt{14} = 12x \sqrt{14} \][/tex]
Thus, [tex]\(-2ab = -12x \sqrt{14}\)[/tex].
Now, combine these results to form the expanded product:
[tex]\[ (x \sqrt{7} - 3 \sqrt{8})^2 = a^2 - 2ab + b^2 = 7x^2 - 12x \sqrt{14} + 72 \][/tex]
So, the product is:
[tex]\[ 7x^2 - 12x \sqrt{14} + 72 \][/tex]
Out of the given options, this corresponds to:
[tex]\[ 7 x^2-12 x \sqrt{14}+72 \][/tex]
Therefore, the correct answer is:
[tex]\[ 7 x^2 - 12 x \sqrt{14} + 72 \][/tex]
To do this, we will use the formula for expanding a binomial squared: [tex]\((a - b)^2 = a^2 - 2ab + b^2\)[/tex]. In our case, [tex]\(a = x \sqrt{7}\)[/tex] and [tex]\(b = 3 \sqrt{8}\)[/tex].
First, let's identify and compute the three terms in the expanded form individually.
1. Calculate [tex]\(a^2\)[/tex]:
[tex]\[ a^2 = (x \sqrt{7})^2 = x^2 \cdot (\sqrt{7})^2 = x^2 \cdot 7 = 7x^2 \][/tex]
2. Calculate [tex]\(b^2\)[/tex]:
[tex]\[ b^2 = (3 \sqrt{8})^2 = 9 \cdot (\sqrt{8})^2 = 9 \cdot 8 = 72 \][/tex]
3. Calculate [tex]\(-2ab\)[/tex]:
[tex]\[ 2ab = 2 \cdot (x \sqrt{7}) \cdot (3 \sqrt{8}) = 2 \cdot x \cdot \sqrt{7} \cdot 3 \cdot \sqrt{8} = 6 \cdot x \cdot (\sqrt{7} \cdot \sqrt{8}) \][/tex]
We know that [tex]\(\sqrt{7} \cdot \sqrt{8} = \sqrt{56} = \sqrt{4 \cdot 14} = 2 \sqrt{14}\)[/tex]. So:
[tex]\[ 2ab = 6 \cdot x \cdot 2 \sqrt{14} = 12x \sqrt{14} \][/tex]
Thus, [tex]\(-2ab = -12x \sqrt{14}\)[/tex].
Now, combine these results to form the expanded product:
[tex]\[ (x \sqrt{7} - 3 \sqrt{8})^2 = a^2 - 2ab + b^2 = 7x^2 - 12x \sqrt{14} + 72 \][/tex]
So, the product is:
[tex]\[ 7x^2 - 12x \sqrt{14} + 72 \][/tex]
Out of the given options, this corresponds to:
[tex]\[ 7 x^2-12 x \sqrt{14}+72 \][/tex]
Therefore, the correct answer is:
[tex]\[ 7 x^2 - 12 x \sqrt{14} + 72 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.